PATHOPHYSIOLOGY, DIAGNOSTIC APPROACHES, AND MANAGEMENT STRATEGIES - Yusupov Mirza Murodovich (World Scientific Research Journal, 2025)
Annotation: Diabetic retinopathy (DR) is a leading cause of vision impairment and blindness among working-age adults worldwide. As a microvascular complication of diabetes mellitus, DR affects the retina’s blood vessels, leading to structural and functional damage over time. The disease progresses through distinct stages, beginning with non-proliferative diabetic retinopathy (NPDR) and potentially advancing to proliferative diabetic retinopathy (PDR), where neovascularization poses a significant threat to vision. This article explores the pathophysiology of DR, outlines current diagnostic methodologies including imaging and clinical grading systems, and examines management strategies encompassing glycemic control, pharmacologic therapies, and surgical interventions. Based on a synthesis of clinical and theoretical data, this paper emphasizes the importance of early detection and comprehensive treatment strategies to minimize the risk of irreversible vision loss in diabetic patients.